India's covid catastrophe. Issue 4 (2nd October 2021) - Saini, Ajay; Nancy,; Malekoff, Andrew
ABSTRACT: In 2020 editor-in-chief (Andrew Malekoff) issued a special call for papers for group work stories on pandemic 2020. Among the 28 stories accepted for the series there were 16 from India, 9 from the United States, 2 from Canada and 1 from Israel. General submissions from the U.S., Canada and Israel were typical for the journal. Atypical are submissions from India. Rather than publish the stories in one special issue of the Journal, he decided to spread them out over several issues through 2022. In the course of organizing the special series (with a December 2021 deadline) he continued communication with a few of the authors from India, with particular interest and concern in the deteriorating situation as 2021 unfolded. Although the present commentary is not about group work per se, it is an update by Ajay Saini, Nancy and Andrew Malekoff on the current state of affairs in India, with some contrast to the situation in the U.S., that offers continuing context for the stories in the series.